The 'lottery' of rape reporting: Secondary victimization and Swedish criminal justice professionals. Issue 1 (2nd January 2021) - Carroll, Caitlin P.
ABSTRACT: Research has established the possibility for rape victim-survivors to experience secondary victimization as a result of encounters with the criminal justice system. However, most of this work is based in Anglo-American countries, with less attention to the issue in the Nordic context. In this article, I report on in-depth interviews with Swedish criminal justice professionals and their perspective on investigating and processing sexual violence cases, as well as interviews with professionals who work directly with rape victim-survivors and their external evaluations of the criminal justice system. While there is a general awareness of the need for an empathetic and sensitive response from police officers and support from the victim's legal counsel, in practice, the process can be a 'lottery' for victim-survivors: while some individual police officers and lawyers are dedicated to victim-centred encounters, others are dismissive or hostile. I discuss policy initiatives, including training, specialization, and required competencies, that institutionalize and standardize victim-centred practices to promote a supportive environment for all sexual violence victim-survivors in the Swedish criminal justice system.